Assessment of the pulmonary CYP1A1 metabolism of mavoglurant (AFQ056) in rat. (3rd August 2018) - Yilmaz, Yildiz; Umehara, Kenichi; Williams, Gareth; Faller, Thomas; Schiller, Hilmar; Walles, Markus; Kraehenbuehl, Stephan; Camenisch, Gian; Manevski, Nenad
Abstract: 1. AFQ056 phenotyping results indicate that CYP1A1 is responsible for the formation of the oxidative metabolite, M3. In line with the predominant assumption that CYP1A1 is mainly expressed in extrahepatic tissues, only traces of M3 were detected in hepatic systems. The aim of this study was to investigate the pulmonary CYP1A1 mediated metabolism of AFQ056 in rat. 2. Western blot analysis confirmed that CYP1A1 is expressed in rat lung albeit at low levels. M3 formation was clearly observed in recombinant rat CYP1A1, lung microsomes and lung tissue slices and was strongly inhibited by ketoconazole in the incubations. As CYP3A4 and CYP2C9 metabolites were only observed at trace levels, we concluded that the reduced M3 formation was due to CYP1A1 inhibition. 3. AFQ056 lung clearance (CLlung ) as estimated from in vitro data was predicted to be negligible (<1% pulmonary blood flow). This was confirmed by in vivo experiments where intravenous and intra-arterial dosing to rats failed to show significant pulmonary extraction. 4. While rat lung may make a contribution to the formation of M3, it is unlikely to be the only organ involved in this process and further experiments are required to investigate the potential metabolic elimination routes for AFQ056.